THE INFLUENCE OF SELF-EFFICACY AND LEADERSHIP ON EMPLOYEE PERFORMANCE AT PT. BTPN SYARI'AH - Nur Ramadhani Lubis; Jasman Sarifuddin Hasibuan (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
This research focuses on the influence of self-efficacy and leadership on employee performance at PT. BTPN. The era of globalization demands an improvement in the quality of human resources as a key factor in achieving the company's vision and mission. PT BTPN Syariah, as part of these efforts, emphasizes the importance of human resource development to enhance performance. Employee performance improvement is pursued through the enhancement of self-efficacy, which is an individual's belief in their own abilities, and effective leadership. This research utilizes a survey method with an online questionnaire as a data collection tool. The results indicate that self-efficacy and leadership positively influence employee performance. Additionally, emotional exhaustion plays a role as a moderating variable, where high levels of employee performance are associated with lower levels of emotional exhaustion. Descriptive data regarding respondent characteristics include gender, age, and educational level. The entire population of facilitators at PT. BTPN Syariah (82 individuals) is taken as a sample using the census technique.